2016
DOI: 10.1037/ccp0000059
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting cognitive processing therapy to improve sleep impairment in PTSD: A randomized controlled trial.

Abstract: Objective Despite the success of empirically supported treatments for posttraumatic stress disorder (PTSD), sleep impairment frequently remains refractory following treatment for PTSD. This single-site, randomized controlled trial examined the effectiveness of sleep-directed hypnosis as a complement to an empirically supported psychotherapy for PTSD (cognitive processing therapy; CPT). Method Participants completed either 3 weeks of hypnosis (n = 52) or a symptom monitoring control condition (n = 56) before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 49 publications
2
82
1
Order By: Relevance
“…Currently, no guidelines exist for including treatment components targeting nightmares in first‐line treatment for PTSD or for selecting the order in which treatments are delivered. One randomized controlled trial offering sleep‐directed hypnosis before cognitive processing therapy for PTSD yielded promising results (Galovski et al., ). In one case study, authors reported successful treatment of one patient with PTSD and nightmares using cognitive processing therapy followed by exposure, relaxation, and rescripting therapy (ERRT), which is an empirically based, trauma‐focused intervention for nightmares that shares some similarities with IRT (e.g., nightmare rescripting; Pruiksma, Molino, Taylor, Resick & Peterson, ).…”
mentioning
confidence: 99%
“…Currently, no guidelines exist for including treatment components targeting nightmares in first‐line treatment for PTSD or for selecting the order in which treatments are delivered. One randomized controlled trial offering sleep‐directed hypnosis before cognitive processing therapy for PTSD yielded promising results (Galovski et al., ). In one case study, authors reported successful treatment of one patient with PTSD and nightmares using cognitive processing therapy followed by exposure, relaxation, and rescripting therapy (ERRT), which is an empirically based, trauma‐focused intervention for nightmares that shares some similarities with IRT (e.g., nightmare rescripting; Pruiksma, Molino, Taylor, Resick & Peterson, ).…”
mentioning
confidence: 99%
“…Recently, two meta‐analyses statistically summarized findings of IR treatments for posttraumatic nightmares and reported large effect sizes for nightmare frequency, sleep quality, and overall PTSD symptomatology (Casement & Swanson, ; Hansen, Hofling, Kroner‐Borowik, Stangier, & Steil, ). A more recent study examined the efficacy of sleep‐directed hypnosis versus a monitoring control condition prior to CPT for PTSD, and found that the hypnosis condition showed significantly greater improvements compared to the control condition in sleep and depression, but not PTSD symptoms (Galovski et al., ). Additionally, hypnosis prior to CPT was effective in improving sleep impairment, but this improvement was not associated with gains in PTSD recovery.…”
mentioning
confidence: 99%
“…Adjuvant exercise also leads to an increased BDNF serum concentration (d = 1.08). Galovski et al (2016) examined the augmentative effect of sleep-directed hypnosis (3x/week over three weeks) preceding CPT (once per week over 12 weeks) compared to daily monitoring of sleep and PTSD symptoms (over three weeks) preceding CPT (control group) in female adults with PTSD. In addition to its effect on PTSD key symptoms and depression, the effect of adjuvant hypnosis on sleep difficulties was assessed.…”
Section: Exercisementioning
confidence: 99%